2014
DOI: 10.5430/jct.v3n2p69
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Study of the Relationship between Distributed Leadership and Organizational Citizenship Behavior: Perceptions of Turkish Primary School Teachers

Abstract: The purpose of this study was to determine the relationship between primary school teachers' perceptions on distributed leadership and organizational citizenship behaviors (OCBs). A total of 258 teachers employed in 14 primary schools located in Kastamonu, Turkey participated in this study. Data of the study was collected through "Distributed Leadership Scale" and "Organizational Citizenship Behavior Scale". Descriptive statistics, Pearson product-moment correlation coefficient and simple regression analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
2
10
0
4
Order By: Relevance
“…Distributed leadership predicts levels of organizational citizenship behavior significantly. Similar to this finding, Kılınç (2014) concluded that distributed leadership is a significant predictor of organizational citizenship behavior in their research conducted with the participation of teachers and Jofreh, Mohammadi and Yasini (2012) with the participation of teachers and school principals. The perception of organizational identity is a significant predictor of organizational citizenship behavior.…”
Section: Findings and Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Distributed leadership predicts levels of organizational citizenship behavior significantly. Similar to this finding, Kılınç (2014) concluded that distributed leadership is a significant predictor of organizational citizenship behavior in their research conducted with the participation of teachers and Jofreh, Mohammadi and Yasini (2012) with the participation of teachers and school principals. The perception of organizational identity is a significant predictor of organizational citizenship behavior.…”
Section: Findings and Discussionsupporting
confidence: 57%
“…2004); 2000'li yıllarda ampirik çalışmalara konu olmuştur (Chen, 2007;Davis, 2009;ESHA, 2013;Gordon, 2005;Grenda, 2011;Heck ve Hallinger, 2009;Oduro, 2004;Singh, 2014;Smith, 2007;Tian, 2011;Williams, 2011). Türkçe alan yazında ise teorik (Baloğlu, 2011a;Baloğlu, 2011b) oldukça sınırlı sayıda ve ampirik olarak (Adıgüzelli, 2016;Ağırdaş, 2014;Arabacı, Karabatak ve Polat, 2016;Baloğlu, 2012;Çakır, 2018;İşcan, 2014;Kılınç, 2014;Korkmaz ve Gündüz, 2011;Özdemir, 2012 Yulianti, 2014). Ancak dağıtılmış liderlik ile örgütsel kimlik arasındaki ilişkiyi inceleyen herhangi bir çalışmaya ulaşılamamıştır.…”
Section: Turkish Studies -Educational Sciencesunclassified
See 1 more Smart Citation
“…In addition, the studies in educational organizations also reveal that leadership behaviours of school administrators have a positive impact on teachers' OCB (Çetin, Korkmaz, & Çakmakçı, 2012;Koh, Steers, & Terborg, 1995;Nguni et al, 2006;Oğuz, 2011). Another research from distributive perspective shows that distributed leadership is a significant and positive predictor of teacher's OCB (Kılınç, 2014).…”
Section: Related Literaturementioning
confidence: 99%
“…Both in Turkish (Çetin et al, 2012;Oğuz, 2011;Yılmaz & Ceylan, 2011), and international literature (Bogler, 2001;Kim, 2002;Hulpia et al, 2009b;Jacobs, 2010;Nguni et al, 2006;Podsakoff et al, 1996) there are numerous studies examining the relationship between different leadership approaches with teachers' JS, OC and OCB. However, there are few research studies (Berjaoui & Karami-Akkary, 2019;Hulpia & Devos, 2010;Hulpia et al, 2009b;Jacobs, 2010;Kılınç, 2014) dealing with distributed leadership and its relationship with the organizational variables.…”
Section: Related Literaturementioning
confidence: 99%